Can the meson cloud explain the nucleon strangeness? - Carvalho, F.; Navarra, F. S.; Nielsen, M. (Amer Physical Soc, 2005)
We use a version of the meson cloud model, including the kaon and the K-* contributions, to estimate the electric and magnetic strange form factors of the nucleon. We compare our results with the recent measurements of the strange quark contribution to parity-violating asymmetries in the forward G0 electron-proton scattering experiment. We conclude that it is very important to determine experimentally the electric and magnetic strange form factors, and not only the combination G(E)(s)+eta G(M)(s), if one does really intend to understand the strangeness of the nucleon.